Anti-epidermal-growth-factor-receptor agents and complete responses in the treatment of advanced non-small-cell lung cancer: a meta-analysis of 17 phase III randomized controlled trials. (30th October 2014) - Qi, Wei-Xiang; Fu, Shen; Zhang, Qing; Guo, Xiao-Mao
Abstract: Purpose: Currently, the anti-epidermal-growth-factor-receptor (EGFR) agents have shown encouraging treatment benefits in patients with various types of solid tumors including non-small-cell lung cancer (NSCLC). Despite these advances, radiological complete response to these therapies is rare. We meta-analyze the incidence of complete response (CR) in advanced NSCLC patients treated with anti-EGFR agents and controls in randomized controlled trials (RCTs). Methods: PubMed, Web of Science, Embase and Cochrane library databases were reviewed for phase III RCTs with EGFR-targeted agents vs. non-EGFR-targeted agents in patients with advanced NSCLC. We calculated the odds ratio of CR in patients assigned to anti-EGFR agents compared to controls. Results: A total of 11, 568 patients from 17 RCTs were included for analysis. The incidence of CR in patients treated with anti-EGFR agents was 1.1% (95% CI, 0.7–1.7%) compared to 0.6% (95% CI, 0.4–0.9%) in control arms. Comparing the different types of anti-EGFR agents, the incidence of CR was 1.9% for gefitinib (95% CI: 1.4–2.6%), 1.4% for cetuximab (95% CI: 0.8–2.7%) and 0.9% for erlotinib (95% CI: 0.6–1.5%), respectively. The use of anti-EGFR agents significantly increased the odds ratio of obtaining a CR (OR 2.12, 95% CI: 1.28–3.49, p  = 0.003) compared to controls. This was found to be higher in treatment arms involving more than 50% of: female patients, patients who had never smoked tobacco, patients of Asian descent or patients with adenocarcinoma or EGFR mutation. No significant differences in ORs were observed in any prespecified sub-groups. Conclusion: Although a CR is rare in advanced NSCLC patients receiving anti-EGFR agents, these drugs significantly increase the OR of a CR compared to controls, especially for patients with EGFR mutations. Further studies are needed to investigate whether the increase of CR with anti-EGFR therapy would be translated into survival benefits.